Search for new heavy particles in the WZ0 final state in pp̄ collisions at √s = 1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
The general search for new heavy particles, X, was presented. The data collected by the Collider Detector at Fermilab showed no evidence for production of X in 110 pb-1. As a function of mass and width of new particle, the general cross section limits were set at 95% C.L. An analysis of results as mass limits on the production of new heavy charged vector bosons was presented.